„We know, that the first of May is an important issue…”: Visual Propaganda in the 1950’s and 1960’s - Somogyvári, Lajos (Per Aspera ad Astra, 2019)
The cited quotation was heard at the session of the Temporary Party Committee of Budapest, on 18 April 1957: not surprisingly, the power chose this event as the first public demonstration, after the repression of the 1956 revolution. The May Day parades had been an important element of the visual culture of the state-party period, showing both continuity and discontinuity between the 1950’s and 1960’s in Hungary. Although the topic of the visual propaganda is a current trend in the contemporary iconography, which fits to the nature of the communist systems, it hasn’t been analysed yet. My study aims to connect a cultural practice (procession on 1 May) with the structuring space (Stalin Square, then Parade Square) and the intentions of the power. These three aspects (time, space and power) get together in the visual representations (photographs), the corpus of the analysis. The interpretation has got a narrow scope, because as the celebration and the place is an iconic one, with multiple meanings, typical (and not reflected) to our historical knowledge. Further questions emerge, like the functions of the statues, rite and celebrations etc., which belong to the fields of anthropology. Photo: Demeter Balla, Fortepan/Hegyi Zsolt